Analisis Gaya Kepemimpinan Kepala Sekolah Dalam Mendisiplinkan Guru Dan Siswa Di SD Muhammadiyah XI Mangkuyudan Surakarta - Fatimah, Lianna, Drs. Rubino Rubiyanto, M.Pd (2017)
This study aims to describe 1) the application of leadership style; 2) leadership style actions; 3) obstacles in disciplining teachers and students; And 4) solutions to overcome obstacles of principals in disciplining teachers and students in SD Muhammadiyah XI Mangkuyudan Surakarta. This research is a qualitative research with phenomenology research design. Data on the principal's leadership style in disciplining teachers and students, with data sources from principals, teachers, students, observation results, and documentation. Resource persons in this research are principals, teachers, and students. Data collection is done by interview, observation, and documentation. The instrument of this study with a list of structured interview questions. Test data validity using triangulation. Data were analyzed using Interactive Analysis. The results of this study show that 1) the principal in disciplining teachers and students applying a democratic leadership style; 2) the actions taken by the principal by: a) deliberating on the teacher in disciplining the students, b) directing the discipline of teachers and students by constantly reminding both structured and spontaneous, c) supervising by the orderly book of teachers and students, d) Participate and model the discipline of teachers and students.discussion e) evaluate every Saturday; 3) there are constraints from teachers, students, and parents; And 4) how to overcome obstacles by doing coaching with teachers, students, and parents.